Pola Asuh Orang Tua dalam Mendidik dan Menumbuhkan Karakter Anak Usia Dini di Desa Ngadimulyo Kabupaten Pasuruan - Chisnulloh, Mukhammad (PT Hakhara Akademia Indonesia, 2023)
The parenting style given to children is to educate and develop character from an early age. When a child grows up, he will grow into a human being with character according to expectations. This research aims to help parents in nurturing and educating children so that they are able to become people with character in living their lives in society. This type of research is qualitative field research and is descriptive in nature. This research uses interview, observation and documentation data collection techniques. The informants for this research were 3 parents who educate children at an early age in Ngadimulyo village using purposive sampling techniques. Data obtained through interviews, observation and documentation methods, to facilitate data analysis, data analysis includes data reduction, namely focusing research data, presenting data and drawing conclusions. Based on the research results, it can be concluded and understood that parenting patterns in shaping the character of early childhood in Ngadimulyo Village have been carried out well. This is proven that children have begun to be able to speak politely and behave well towards everyone, have a religious attitude, are independent, in everyday life.